ICF or ICPC: what is missing for primary care? - Araújo, Eduardo Santana de; Neves, Sebastião Fernando Pacini (Acta Fisiátrica, 2014)
The International Classification of Primary Care (ICPC) has often been confused with the International Classification of Functioning, Disability and Health (ICF) because it is a tool that indicates problems related to health, but which are not diseases. Although its importance be recognized in primary care, the ICPC points, for example, the reasons for contact with health services, clinical information and some interventions. In none of these respects, the ICPC addresses the issue of functioning and disability, either, the relationship of environmental factors on human performance. ICPC is a mere intermediary for the International Statistical Classification of Diseases and Related Health Problems (ICD), it does not include all information necessary for a diagnosis of health status or the health determinants. Thus, managers need to thoroughly know the ICF, since it is a reference classification of the World Health Organization and the real complement for the ICD to population data. The ICF contains the necessary tolls to stimulate a cross-sectoral work, but it has been done only for specialized care, what leave aside all the potential of its application in primary care.